Research gap strategies in article introductions of different rank applied linguistics journals - Safnil Arsyad; Yetti Zainil (Universitas Syiah Kuala, 2023)
Research gap (RG) becomes an important rhetorical work in research article introductions in all fields, especially in a competitive research publication atmosphere. A research article (RA) submitted to a reputable journal may be rejected because the writers fail to show the ‘niche’ in reviewing previous relevant studies to justify their research project. This research aims to find how writers in Applied Linguistics (AL) published in international journals of different quality in terms of their quartile value address the novelty in their journal article introductions. Forty articles were selected from eight different reputable international journals in AL of different tiers for the corpus of this study. The content analysis method under the umbrella of the qualitative approach was applied in the data collection and analysis. Six RG strategies, as suggested by Arianto et al. (2021), were used as a model for analysis and then the linguistic features used by the writers in realizing the RGs. The results show that among the six different RG strategies, the most frequently used by international writers are Strategy 2 (inadequate research) and Strategy 4 (contradictive/conflicting evidence). Among the four groups of RAs, those published in Quartile 1 journals used the most frequent strategies. The frequent linguistic features used by international writers are adversative conjunctions and adjective-modifying nouns to signal their RG strategies. To improve the quality of an article introduction, writers, especially novice writers, should use multiple strategies with the appropriate linguistic features.